Leadership Competencies and Role Effectiveness of Managers: A Case Study in Selected Public Sectors of Quezon City for Basic and Applied Management Research Journal - Bayona, Anthony Julius F.; Malang, Bernandino P.; Malang, Jocelyn DS.; Poso, Kathrine Ann L.; Facturanan, Marc Dave (Future Science / FSH-PH Publications, 2026)
Leadership serves as a critical factor of efficiency, productivity, and overall success of an organization, particularly within the public sector where it directly influences the quality of governance and service delivery. Public sector leaders/managers in the Philippines encounter distinct challenges arising from bureaucratic structures, constraints in resources, and the increasing demand for a more efficient, resilient and responsive governance. Thus, this study seeks to examine the relationship between leadership competencies and managerial role effectiveness among selected public sector managers in Quezon City, Philippines. A researcher-made structured survey questionnaire was administered online to forty-seven (47) purposively selected respondents. Descriptive statistics and Spearman’s correlational matrix was used to analyze the data. Results revealed that participants generally demonstrated high to very high levels of leadership competency and role effectiveness, with weighted mean scores of 4.34 and 4.26, respectively. Given the results, this study found a strong positive correlation between leadership competency and role effectiveness. Capacity-building programs and developmental interventions were recommended to address low ratings in the change management and adaptability, and coaching and performance management competencies. Further research is recommended to include multiple local or national government agencies for improved generalizability.